Access to Education and Teenage Pregnancy - Martin Foureaux Koppensteiner; Jesse Matheson (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2016)
Little is known about the causal impact of education opportunities on the decision of young women to have children. Expanding education opportunities may lead to a greater number of young women putting off childbearing until after their teenage years. In this study we look at the effect of one of the largest secondary school expansions on record, providing quasi-experimental evidence to uncover the causal impact of education opportunity on teenage fertility. After achieving near universal enrolment in primary education in the mid- 1990s, Brazil went through an ambitious program of expanding secondary schooling. Between 1996 and 2009 more than 10,269 secondary schools were introduced, increasing the average enrolment rate for teens age 15 to 19 from 21% to 48%. We combine data from the Brazilian School Census, and Brazilian Vital Statistics data capturing 45 million live births by age of mother into an extraordinarily rich data set. Plausibly exogenous variation in the introduction of schools across municipalities over time is used to estimate the effect of education opportunity on teenage births. We find a significant negative effect of secondary school availability on teenage pregnancy. Our results suggest that the addition of one school at age 15 will reduce average cumulative births by 19 by, on average, 4.4 births or 4.6% relative to the mean. These results suggest that the expansion in secondary schools across Brazil can account for roughly 27% of the large decline in teenage childbearing observed between 1997 and 2009 in Brazil.
Keywords: I20; I26; J13; 330; Secondary education; teenage pregnancy; Brazil